2014
DOI: 10.1016/j.parkreldis.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nervous system involvement in Parkinson's disease: Evidence and controversies

Abstract: It is currently debated whether PN is an intrinsic disease-related feature, a consequence of levodopa treatment or both. In this review, we will discuss the different hypotheses, as well as our perspective on open issues and controversies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 57 publications
0
47
0
3
Order By: Relevance
“…Fourty to fifty percent of PD patients also develop anxiety which can occur at any stages of the disease [80,120]. Emerging evidence suggests that PD related pathology may occur in the peripheral nervous system (PNS), but due to lack of drug-naïve groups it is difficult to distinguish if the PNS neuropathology is a consequence of PD or pharmacological PD treatments [27]. In light of wide-ranging non-motor symptoms, and presence of pathology outside of the CNS, PD is increasingly considered a systemic rather than a disease of basal ganglia.…”
Section: Pathology Overlap Between Tbi and Pdmentioning
confidence: 99%
“…Fourty to fifty percent of PD patients also develop anxiety which can occur at any stages of the disease [80,120]. Emerging evidence suggests that PD related pathology may occur in the peripheral nervous system (PNS), but due to lack of drug-naïve groups it is difficult to distinguish if the PNS neuropathology is a consequence of PD or pharmacological PD treatments [27]. In light of wide-ranging non-motor symptoms, and presence of pathology outside of the CNS, PD is increasingly considered a systemic rather than a disease of basal ganglia.…”
Section: Pathology Overlap Between Tbi and Pdmentioning
confidence: 99%
“…We addressed the limitations of the previous meta-analysis by performing a comprehensive and extensive literature search that evaluated RCTs using appropriate criteria, including a qualitative analysis of RCTs and the use of the GRADE approach to determine the quality of evidence. The quality of the studies was considered only moderate or low based on the following parameters: [1] the included trials were reported as randomized, double-blind trials but did not provide additional details; [2] moderate variation in baseline variables was observed among the studies; [3] some comparisons exhibited heterogeneity; and [4] creatine was used in combination with CoQ10 or minocycline [18, 22]. The RCTs were generally of high quality, although we did include RCTs that involved diverse risks.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, these studies lacked long-term assessments of key indicators, such as 5- or 10-year patient survival rates. Some of the trials were quite heterogeneous, with several reasonable explanations for this finding: [1] the trials used different doses of creatine; [2] two of the trials [18, 22] used CoQ10 or minocycline as a co-intervention; [3] all of the trials were reported as RCTs but did not provide additional details; [4] the intervention was not confined to a single variant, which may have had indirect effects; and [5] one study [19] reported a high drop-out rate (greater than 20%. )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD neuropathology is characterized by the loss of dopaminergic neurons and the presence of Lewy bodies (LBs) in surviving neurons [6,7]. LBs contain fibrils composed of alpha-synuclein, a small protein involved in synaptic vesicle trafficking and neurotransmitter release [7] but also in more widespread functions, including the triggering neuroinflammatory processes [8].…”
Section: Introductionmentioning
confidence: 99%